(untitled) (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
This article examines the agrarian policy of the Soviet state and the development of cotton cultivation in Uzbekistan during the 1930s. The history of cotton growing and processing in the country, its significance, and its influence on other sectors of the economy are analyzed. The article is based on archival documents from the funds of the National State Archive of Uzbekistan, scientific research of foreign and local scholars, monographs and treatises, and contains conclusions relevant to the topic under study.